PENDAMPINGAN PEMULIHAN KONDISI PETERNAKAN AYAM RAS PETELUR PASCA GEMPA DI KABUPATEN LOMBOK UTARA - Dwi Kusuma Purnamasari; Syamsuhaidi Syamsuhaidi; Erwan Erwan; Ketut Gede Wiryawan (Universitas Mataram, 2019)
An earthquake that occurred from the end of July to the end of August 2018 in the province of NTB has detroyed not only residential buildings, offices, schools, religious buildings, but also livestock houses, especially the houses and cages. Almost all districts in the NTB province was affected by the earthquake and the worst affected districts were North Lombok and East Lombok. The Norty Lombok Regency is currently experiencing total paralysis both in the fields of education, government and economics and tourism. One business that requires rapid handling in the field of animal husbandry is for egg production. There are 26 poultry farmers who are members of the